ChemInform Abstract: Expeditious One‐Pot Three Component Synthesis of N‐Aryl Dithiocarbamate Derivatives Using Mesoporous Cu‐Materials. Issue 28 (July 2015) - Payra, Soumen; Saha, Arijit; Peng, Rui; Wu, Chia‐Ming; Koodali, Ranjit T.; Banerjee, Subhash
Abstract It is demonstrated, that copper supported on MCM‐48 efficiently catalyzes the reaction of aromatic amines, carbon disulfide, and esters or amides to form dithiocarbamates in short reaction times and under mild conditions.